PENGARUH HUKUMAN FISIK TERHADAP PEMBENTUKAN DISIPLIN SISWA DI MTS PONDOK PESANTREN DARUL QURAN KAMPAR - Gustiawan, Ade Gustiawan Ade (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research was based on physical punishments to discipline students according to Islamic education with certain limitations. Pondok Pesantren (boarding school) as an educational institution of Islam, still allow ways to punish physically in disciplining students, regardless of the issue of human rights violation. Pondok Pesantren Darul Quran cling to the teachings of the Quran and Hadiths about how to punish their students. The formulation of the problem was ‘is there any effect of physical punishment to the establishment of studens’ discipline in MTs Pondok Pesantren Darul Quran Kampar?’. This research was aimed to discover the effect of the physical punishment to establishment of students’ discipline in MTs Darul Quran Kampar. The population was 22 teachers and 144 students and the sample was 22 students by proportional random sampling technique. The data were collected by a questionnaire consisting of 15 questions for teachers about the physical punishment (X variable) and 19 questions about the students’ discipline (Y variable). The data were analyzed by quantitavive descriptive using SPSS 18.0 version. The research finding showed that the hypothesis of there is the effect of physical punishments to the establishment of students’ discipline in MTs Darul Quran Kampar was rejected. The finding also proved by the hypothesis tests between X variable to Y variable, the results were Fcalculate 0,667 and Ttable 4,35 that found from critical values for the F distribution N=22, significant level 5%, so Fcalculate < Ftable or 0,667<4,35. In addition, the hypothesis was rejected that there was no effect of the physical punishments to the establishment of students’ discipline in MTs Darul Quran Kampar.Keywords: Physical punishment, Students’ discipline